2007
DOI: 10.1007/s00439-007-0372-9
|View full text |Cite
|
Sign up to set email alerts
|

A TNF region haplotype offers protection from typhoid fever in Vietnamese patients

Abstract: The genomic region surrounding the TNF locus on human chromosome 6 has previously been associated with typhoid fever in Vietnam. We used a haplotypic approach to understand this association further. Eighty single nucleotide polymorphisms (SNPs) spanning a 150 kb region were genotyped in 95 Vietnamese individuals (typhoid case/mother/father trios). A subset of data from 33 SNPs with a minor allele frequency of >4.3% was used to construct haplotypes. Fifteen SNPs, which tagged the 42 constructed haplotypes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 35 publications
(51 reference statements)
1
12
0
Order By: Relevance
“…A community-based, case-control study in Indonesian patients with enteric fever demonstrated no association at three TNF and TNF receptor superfamily, member 1A (TNFRSF1A) genetic variants 38 . By contrast, a case-control study of enteric fever in a Vietnamese population identified a protective effect of an MHC class III haplotype, which included the TNF gene, against enteric fever 59 . Patients with enteric fever and the protective haplotype were shown to produce statistically significantly less TNF ex vivo on whole blood stimulation with LPS on day four of disease 59 .…”
Section: Haematocritmentioning
confidence: 96%
See 1 more Smart Citation
“…A community-based, case-control study in Indonesian patients with enteric fever demonstrated no association at three TNF and TNF receptor superfamily, member 1A (TNFRSF1A) genetic variants 38 . By contrast, a case-control study of enteric fever in a Vietnamese population identified a protective effect of an MHC class III haplotype, which included the TNF gene, against enteric fever 59 . Patients with enteric fever and the protective haplotype were shown to produce statistically significantly less TNF ex vivo on whole blood stimulation with LPS on day four of disease 59 .…”
Section: Haematocritmentioning
confidence: 96%
“…By contrast, a case-control study of enteric fever in a Vietnamese population identified a protective effect of an MHC class III haplotype, which included the TNF gene, against enteric fever 59 . Patients with enteric fever and the protective haplotype were shown to produce statistically significantly less TNF ex vivo on whole blood stimulation with LPS on day four of disease 59 . However, this finding should be interpreted with caution, as this effect was not seen in a better-powered GWAS of enteric fever in the same population 6 .…”
Section: Haematocritmentioning
confidence: 96%
“…Resistance to typhoid fever is, however, associated with a protective haplotype in the TNF region on chromosome 6, within the MHC class II locus. 9 HIV does not seem to be associated with an increased susceptibility to, or worse outcome of typhoid fever. Gotuzzo et al described eight patients with HIV and typhoid in Peru, four with unusually severe diarrhoea or colitis, and two with relapse after treatment.…”
Section: Typhoid Fever In Immunocompromised Adultsmentioning
confidence: 86%
“…Of interest, HLA-DR haplotypes were associated with protection from severe enteric fever among Indonesian patients, although this could not be linked with TNF-␣ production capacity (31). Further analysis of the Vietnamese population again suggested that a haplotype in the TNF region gives protection against enteric fever, but the causative disease locus remains to be determined (32). In a recent genome-wide association study of patients in Vietnam and Nepal with blood culture-confirmed enteric fever, a strong association was found for HLA-DRB1 as a major contributor to resistance against enteric fever, presumably through antigen presentation (33).…”
Section: Epidemiology and Clinical Aspects Typhoidal Salmonellamentioning
confidence: 98%